Konsep Ahli Waris Pengganti Dalam Hukum Kewarisan Islam dan Implementasinya Dalam Hukum Adat dan Kompilasi Hukum Islam - Lia Murlisa (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2017)
Heir substitution term is not available neither in al-Qur’an nor hadits, but it is the result of ijtihad. It was derived from considering the position of the grandchild (either from the woman or man side) and also the woman whose parents have passed away. The grandchild is not a part of the heir that was determined in al-Qur’an. However, its position is considired important in order to replace the parents position. The legal ground in determining the heir substitution is for the sake of justice. In Islamic law compilation article 185, it is stated that heir substitution are only for the direct inherit. Otherwise, for Indonesian customary law, the inheritance (estate) was considered as the basic finansial for the heir.